HUBUNGAN IKLIM ORGANISASI DENGAN WORK ENGAGEMENT PADA KARYAWAN PT. PLN (PERSERO) UPP KITRING KALBAGTENG 3 CABANG SAMPIT - Nabila Tri; Saladin Ghalib; Fitriyadi Fitriyadi (Lambung Mangkurat University, 2021)
This Organizational Climate Relationship with Work Engagement of PT. PLN (Persero) UPP Kitring Kalbagteng 3 Sampit Branch. This study aims to examine Organizational Climate (X) with Work Engagement (Y) on the employees of PT. PLN (Persero) UPP Kitring Kalbagteng 3 Sampit Branch. The research approach used is a quantitative approach. Samples taken as many as 36 respondents with saturated sampling technique. Data collection uses a questionnaire, while data analysis uses product moment correlation. The results of the study prove that Organizational Climate is significantly related to Work Engagement of 0.711% or 71.1%. Based on this research it can be concluded that the better the Organizational Climate will be related to the increase in Work Engagement of PT. PLN (Persero) UPP Kitring Kalbagteng 3 Sampit Branch. Keywords: Organizational Climate and Work Engagement